Simulasi Perubahan Energi Per Bit Dan Derau Terhadap Jumlah Kanal Dan Cakupan WCDMA - Alfin Hikmaturokhman; Hesti Susilawati; Tantiningrum Niken (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2010)
Eb/No parameter is the measure of signal to noise ratio for a digital communication system, it is measured at the input to the receiver and is used as the basic measure of how strong the signal is, or in other words Eb/No indicates the fluctuation of received signal strength in the receiver. Eb/No is affected by several factors, such as speed of mobile station, propagation environment and bit rate. The variations of Eb/No value will affect to the number of offered channel and coverage in WCDMA. The impact of the variation of Eb/No value could be recognized in the result of the calculations. The purpose of this research is to build simulation models by using Delphi to view and analyze the influence of Eb/No of total channels and WCDMA coverage. The results from simulation analysis showed that the larger of Eb/No and bit rate used, the number of channels on offer will be smaller and the value of BS is low sensitivity, which means loads of traffic will also offer little that would cause the quality to be better systems and transmit power MS becomes more lower in order to maintain the value of Eb/No to avoid the drop call.